The Polish Folk Ensembles of Winnipeg: Shaped by Atlantic Cultural Currents - Smith, Muriel (MUSICultures, 2013)
Two Polish folk ensembles of Winnipeg share ancestral roots and a similar purpose as purveyors of Polish Canadian culture, yet they are disparate in their approach; one centres on maintaining an authentic heritage, the other on relevance. By examining their entwined histories, I propose that processes of globalization involving the transfer of information, ideas and cultural perspectives across multiple generations and numerous transatlantic Polish migrations have reformulated and re-signified the expressive practices of these two groups. This study contributes to musicological research considering transatlantic cultural flows between ancestral homelands and the Americas.